Gambaran Capaian Persiapan Akreditasi Versi 2017 Bagian Kompetensi dan Kewenangan Staf (KKS) Standar 6 di Sub Bagian Kepegawaian Rumah Sakit Umum Kabupaten Tangerang Dengan Perbandingan Hasil Akreditasi Versi 2012 - Susi Shorayasari Zuhron; Boy S. Sabarguna; Salwa Fadhila (MEDICORDHIF Jurnal Rekam Medis, 2018)
ABSTRACT Background: Hospital Accreditation is the recognition of the hospitals provided by an accredited institution of independent organizers stipulated by the minister of health. The research method used is search checklist document, interview and observation with approach of cuantatif with 1 informant 453 document of ownership of civil servant. Result of research description of hospital preparation achievement in facing accreditation of 2017 version that is 32%. Qualification is not fulfilled 1 (1%), fulfilled part 363 (80,1%) and fulfilled complete 89 (19,6%) with result score 0 job description that is not fulfilled 90 (19,9%), partially fulfilled 0 (0%) and complete fulfillment of 363 (80,1%) with result of score 10. Recruitment process that is not fulfilled 453 (100%), partially fulfilled 0 (0%) and fulfilled 0 (0%) with result score 0 the job is not fulfilled 215 (47,7%), fulfilled part 0 (0%) and fulfilled 238 (52,5%) with score result 5. Performance appraisal that is not fulfilled 59 (13%), fulfilled part 376 (83% ) and fulfilled 18 (4%) with score of 0. Copy of Certificate that is not fulfilled 143 (31,6%), partially fulfilled 0 (0%) and fulfilled 310 (68,4%) with result score 5. File update not fulfilled 0 (0%), fulfilled part of 453 (100%) and fulfilled 0 (0%) with result of score 0 Total unmet conclusion is 30,4%, fulfilled part 37,6% and complete complete 32%. From the data it can be concluded that RSU Kab. Tangerang has not fulfilled the graduation requirement of the standard of graduation ≥80%. Keywords: Hospital Accreditation of 2017 version, Preparation Picture, Tangerang District Hospital